2021
DOI: 10.5937/scriptamed52-29376
|View full text |Cite
|
Sign up to set email alerts
|

Association of PPARG rs3856806 C>T polymorphism with body mass index, glycaemia and lipid parameters in Serbian adolescents

Abstract: Background/Aim: Peroxisome proliferator-activated receptor gamma (PPARg) belongs to a family of nuclear hormone receptors and ligand-activated transcription factors. PPARG gene is expressed in many tissues including adipose tissue where it plays a crucial role in differentiation of adipocyte, insulin resistance, blood glucose levels and lipid metabolism. The aim of the study was to examine the association of rs3856806 polymorphism with the body mass index (BMI), fasting glucose levels and lipid parameters in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(44 reference statements)
0
2
1
Order By: Relevance
“…These findings closely resemble results obtained in our study, in which CC genotype ( PPARG rs3856806) was significantly associated with higher mean HDL-c values and carriers of variant alleles of both PPARG rs3856806 and PPARGC1A rs8192678 presented significantly lower serum HDL-c levels. Still, the authors also report higher fasting blood glucose levels within the same CT and TT genotype group ( 57 ), which we could not trace in our study. Contradictorily, Fan et al reported a correlation between minor allele variants of rs3856806 and elevated LDL-c levels in Chinese adults ( 61 ).…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…These findings closely resemble results obtained in our study, in which CC genotype ( PPARG rs3856806) was significantly associated with higher mean HDL-c values and carriers of variant alleles of both PPARG rs3856806 and PPARGC1A rs8192678 presented significantly lower serum HDL-c levels. Still, the authors also report higher fasting blood glucose levels within the same CT and TT genotype group ( 57 ), which we could not trace in our study. Contradictorily, Fan et al reported a correlation between minor allele variants of rs3856806 and elevated LDL-c levels in Chinese adults ( 61 ).…”
Section: Discussioncontrasting
confidence: 87%
“…Queiroz et al reported no association for PPARG rs1801282 and several anthropometric and metabolically-related parameters (BMI, WC, total cholesterol, LDL/HDL cholesterol, insulin, and HOMA-IR, body fat percentage, birth weight, systolic blood pressure), within a research article conducted on Brazilian children and adolescents ( 56 ). Two other reports described an insignificant impact of PPARG rs3856806 polymorphism on BMI value variations among children and adolescents ( 57 , 58 ). In our study we failed to identify an association between three polymorphisms of PPARG and children with overweight and obesity.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Also, in the period of adolescence, boys tend to have more physical activities than girls, which might be one of the reason for difference in BMI (23). On the other side impact of increased secretion of testosterone in adolescent boys, leads to the higher lipase activity in the liver, which causes lowering of the lipid parameters as well as lower BMI (24). However, many of these studies measured the circulating level of protein in particular populations, but association of rs4644 genotype was not addressed.…”
Section: Discussionmentioning
confidence: 99%